Pengaruh Konflik Peran Terhadap Kinerja Dengan Self Efficacy Sebagai Variabel Moderasi - Muallifah, Masrurul; Astuty, Isthofaina (Jurnal Manajemen Bisnis, 2016)
This research aims to analyze the influence of Role Conflict on Performance with Self Efficacy as a Moderation on the set of Variables the student Department of the Faculty of Economics and Business of Muhammadiyah University of Yogyakarta (HIMAMA, HIMA and HIMIE). The population or a sample that is used is the caretaker and the third member of the organization which amounted to 156. The data used in this research is the primary data collected through the distribution of questionnaires to our respondents. Analysis of testing data using validity and reliability testing, regression and moderated regression analysis, and test the assumptions of the classical test of normality, multikolonieritas, and heteroskedastisidas. The results showed a negative effect and role conflict significantly to the performance of the organization means that the higher role conflict occurs then the performance is declining. Meanwhile, self efficacy are able to moderate the influence of role conflict on performance where self efficacy are positive and significant effect on performance of the organization. This means the higher self efficacy which belonged to someone then its performance will be better and is able to dampen the conflict of roles.